Restoring Democracy: Australian Responses to Military Coups in Fiji (Journal of International Studies, 2015)
This article examines Australian responses to successive military coups in Fiji as well as the 2014 Fijian election. In each of Fiji’s three military coups, Australia failed to strike an appropriate balance between simultaneously condemning these military takeovers and taking positive steps toward restoring Fiji to normal democratic processes. Accordingly, this article argues that Australia has habitually viewed Fiji’s military coups through a broader strategic lens which has done little to encourage political change in Suva. Recent positive steps by the Abbott government to normalise relations and assist with Fiji’s 2014 election inspired some degree of confi dence about the future of Fiji and its relationship with Australia. Nevertheless, for Australia to fi nd long-term stability in Fiji, the Abbott government must learn from past mistakes, tread cautiously, and encourage stronger dialogue between the two countries.